2020
DOI: 10.1021/acs.langmuir.0c01912
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification and Adhesion Mechanism of Isotactic Polypropylene with Low-Energy Electron-Beam Treatments

Abstract: Recently, smaller-size electron-beam (EB) accelerators have offered EB irradiation in laboratory systems. Therefore, polymer surface treatments with low-energy EB have been developed in the past years. For high adhesion strength, low-energy EB treatment is also a promising method in comparison to plasma surface treatment. In the plasma treatment, the mechanism of the effect on the adhesion properties has been proved and the excess treatments led to the formation of a weak boundary layer and reduction of adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Weak bonding at the interface adversely affects the various properties of PP-based nanocomposites and metal/resin bonding materials, such as mechanical properties, gas permeability, and thermal conductivity. Therefore, various conventional surface treatments of PP, such as cold plasma treatment, low-energy electron-beam treatment, ion-beam irradiation, and so on, have been explored to archive strong bonding between the PP and metals or other polymeric materials. These surface treatments improve the adhesion between PP and metal surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…Weak bonding at the interface adversely affects the various properties of PP-based nanocomposites and metal/resin bonding materials, such as mechanical properties, gas permeability, and thermal conductivity. Therefore, various conventional surface treatments of PP, such as cold plasma treatment, low-energy electron-beam treatment, ion-beam irradiation, and so on, have been explored to archive strong bonding between the PP and metals or other polymeric materials. These surface treatments improve the adhesion between PP and metal surfaces. …”
Section: Introductionmentioning
confidence: 99%
“…This owes to the fact that the plasma treatment process occurs near the surface. Moreover, the systemic plasma treatment for adhesion characteristics was indicated that the excess treatments result in creating a poor boundary layer and reducing the adhesion strength [37][38][39]. In the textile modification, unlike other radiation methods such as plasma [40,41], corona charges [42], or microwave radiation, [43] it was reported that the e-beam penetration occurred in the entire volume of the fibers, as well as, affected the whole portions of the fiber substructure [36,44,45].…”
Section: Advantages Of Ebi Technologymentioning
confidence: 99%
“…In previous studies, the influence of electron beam irradiation on the molecular structure, crystallization, rheology, and mechanical properties of PP has been investigated in detail. [26][27][28][29] For example, Helmut Münstedt's group investigated the rheological properties and molecular structure of electron-beam irradiated PP. The results showed that irradiation reduced the molecular weight of PP due to chain scission.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the free radicals were formed for the electron‐beam irradiated PP, which formed covalent bonds and improved interfacial strength between substrates and adhesives. [ 27 ] M. Stephan's group irradiated PP in a molten state with electron‐beam. Compared with solid‐state irradiation, a higher branching degree was achieved under the molten state irradiation process.…”
Section: Introductionmentioning
confidence: 99%